Effects of electromyostimulation and resistance training on batting velocity in softball / Raja Nurul Jannat Raja Hussain - Raja Hussain, Raja Nurul Jannat (2019)
Having a fast batting velocity is an important characteristic for all softball players. Previously, traditional resistance training and dry swing training were commonly used by coaches to develop strength and batting velocity. Recently, whole-body electromyostimulation (WB-EMS) has been employed as an alternative training method in improving strength. However, it is not fully explore in improving sport specific movement such as batting velocity. Therefore, this study aimed to investigate the effectiveness of eight weeks of WB-EMS training on strength and batting velocity among female collegiate softball players. Four different training modes namely dry swing and resistance training (DS&RT), dry swing and whole-body electromyostimulation (DS&EMS), dry swing concurrent with whole-body electromyostimulation (DSEMS) and dry swing only (DS) were conducted in this study. Results after eight weeks showed that all of the training groups improved in upper body strength (DS&RT: 28.71%, DS&EMS: 9.90%, DSEMS: 6.74%), lower body strength (DS&RT: 19.51%, DSEMS: 14.15%, DS&EMS: 9.44%), and torso rotational strength (DS&RT: 29.15%, DSEMS: 27.60%, DS&EMS: 20.22%). However, dry swing group showed only an improvement in torso rotational strength (9.37%). Having a greater strength helps to generate fast batting velocity and this study demonstrated that dry swing and traditional resistance training produced greater improvement in muscular strength compared to WB-EMS training. On the other hand, dry swing concurrent with whole-body electromyostimulation generated fastest batting velocity (10.5%) compared to DS&RT (8.43%), DS&EMS (3.67%), and DS (0.3%) group. This indicates that concurrent training was able to improved sport specific movement. Furthermore, this DSEMS training only takes about 20-25 minutes of training time per session; hence, it is able to serve as an alternative training method for coaches who have time constraint in preparing their athletes specifically in strength and batting velocity. In conclusion, this study suggests that for coaches who want to improve their players’ strength, traditional resistance training should be consider to be applied in their training program. However, for coaches who focus on improving strength and direct to sport specific movement, dry swing concurrent with whole-body electromyostimulation should be include in training program. Since this study measured on the effectiveness of WB-EMS on strength and batting velocity, in future, it is recommended to measure the effectiveness of WB-EMS on other physical and sport’s specific movements.